Ventral tegmental area GABAergic neurons induce anxiety-like behaviors and promote palatable food intake. (15th August 2020) - Chen, Li; Lu, Yi-Ping; Chen, Hui-Yun; Huang, Sheng-Nan; Guo, Yu-Rou; Zhang, Jing-Yuan; Li, Qi-Xuan; Luo, Chen-Yu; Lin, Shao-Wei; Chen, Zhao-Nan; Hu, Li-Huan; Wang, Wen-Xiang; et al.
Abstract: The obesity epidemic is a global problem and a great challenge for public health. Overconsumption of food, especially palatable food, is the leading cause of obesity. The precise neural circuits underlying food overconsumption remain unclear and require further characterization. In the present study, we showed that Ca 2+ signals of GABAergic neurons within the ventral tegmental area (VTA) increased after the onset of food intake, especially high-fat or high-sugar chow. Optogenetic activation of VTA GABAergic neurons evoked immediate eating of palatable food and significantly increased palatable food intake in satiated mice. Photoinhibition of VTA GABAergic neurons suppressed palatable food intake. Surprisingly, photoactivation of VTA GABAergic neurons suppressed the intake of standard chow in fasted mice, but did not reduce the duration of eating of standard chow. Moreover, we found that photoactivation of these neurons drove a series of anxiety-like behaviors in the open field, elevated plus maze, and marble-burying test. Additionally, we found that VTA GABAergic neurons sent abundant projections to the lateral hypothalamus and photoactivation of GABAergic VTA terminals in the lateral hypothalamus induced overconsumption of palatable food, but not anxiety-like behaviors. Taken together, our results illustrate that GABAergic VTA neurons are a key node in the neural circuitry underlying anxiety-like behavior and over-feeding of palatable food, and that over-excitation of GABAergic VTA neurons may underlie clinical diseases related to anxiety and obesity. Highlights: Calcium signal of VTA GABAergic neurons is increased during the feeding of palatable food and various anxiogenic stimuli. Photoactivation of VTA GABAergic neurons increases palatable food intake and drives anxiety-like behavior in mice. Photoactivation of VTA-LH GABAergic pathway promotes palatable food consumption, but not anxiety-like behavior.